Ankle reconstruction and microfracture chondroplasty in a basketball player - Lumpkin, K. J.; Galley, B. (Journal of Athletic Training, 2019)
A 20 year old collegiate female athlete with a history of multiple ankle sprains in high school presented with lateral ankle pain after an inversion stress during an event in November 2017. Although the athlete was able to return to play (RTP) with tape, the ankle pain persisted. Initial evaluation by the certi? ed athletic trainer found a negative anterior drawer and Kleiger's test but positive for inversion stress test. Point tenderness was noted on the calcaneo? bular (CF) ligament and inferior to the medial malleolus. Swelling was found over the CF and posterior to lateral malleolus. After a 7 day rehab of RecoveryPumps, GameReady, underwater treadmill, AROM, RROM and PWB, the athlete was able to RTP for 1 hour of contact. At day 10, she was RTP without restrictions. Athlete reported zero pain during participation but slight pain after play. A ? are up of pain occurred in January, 7.2 weeks after onset. Differential Diagnosis: Ostoechondritis dissecans (OCD), CAI, ? bular stress reaction, ? bular fracture, avulsion fracture, peroneal strain and/or peroneal tendinitis. Treatment: Controlled ankle motion (CAM) walker was used as needed for ADL's. X-ray was negative for fracture and physician recommended prednisone for pain and in? ammation. Treatment during full participation included strengthening, soft tissue massage, foam rolling, taping during participation and ice post play. Due to chronic ankle pain post-season, athlete followed up with the physician in March 2018 (4 months after injury). An MRI was ordered. These results showed a stage 3 OCD at the lateral talar dome, anterior-talo? bular ligament partial tear, and Deltoid (anterior-portion) ligament tear with slight avulsion fracture. Athlete then consulted with an Orthopedic about surgery or conservative care. After 6 weeks of rehabilitation with little success, a repeat MRI was scheduled because of an increase in insidous lateral ankle pain. A repeat x-ray denoted an osteophyte of the distal anterior, medial malleolus which lead the patient and physician to elect for ankle reconstruction and microfracture chondroplasty (MC). The MC and osteophyte removal surgery occurred in August (9 months post injury) and the Broström reconstruction was a second surgery in September. The athlete was restricted to NWB for 4 weeks between surgeries. After the reconstruction, 6 weeks of NWB and casting was indicated. Next the athlete was placed in an aircast and allowed to WB while ambulating, however, she was restricted from bicycling and ankle exercises, other than light theraband. Full RTP is yet to be determined. The rehabilitation plan is 3 months of progressive exercises, proprioceptive activities, and sports speci? c drills prior to RTP in March, if no complications develop. Uniqueness: While 15% of sports injuries occur in the ankle, the prevalence of OCD is increasing in athletes. Cartilage defects are present in 50% of ankle sprains while CAI is found in approximately 23% of those athletes1. Lateral ankle reconstruction for CAI is more prevalent but more outcome data is needed. Since surgical strategies for OCD vary without one being superior more research is needed in this area2. Conclusions: Although this athlete was able to continue play for one season with mild ankle pain, it is important to continue to follow up with specialists when pain persists. This case demonstrates the excellent care provided to an athlete who struggled with chronic ankle pain. This athlete reports wearing ankle braces and tape during high school participation and 2 college seasons. The continuous stress placed on competitive young athletes could be a factor in the rise of ankle reconstructions during college. After two surgeries and progressive rehabiltation for 7 months (1.3 years post injury), it is suspected that this athlete will have a full RTP.